A concert-tribute in celebration of Lucresia Kasilag's golden anniversary as a musician - Kasilag, Lucresia (Animo Repository, 1990)
DLSU hosted a concert-tribute in celebration of Lucresia Kasilag's golden anniversary as a musician. Kasilag is a National Artist and former president and artistic director of the Cultural Center of the Philippines. Highlight of the concert was the premiere of Isang Oda sa Pamantasan ng De La Salle a commissioned work by Kasilag, which was performed by the DLSU Chorale.